Performance of Fixed-Bed Adsorption Reactor for Total Chromium Removal from Batik Wastewater Using Bioadsorbents and Zeolite - Winda Nurmalia Rizqy; Raden Kokoh Haryo Putro; Praditya Sigit Ardisty Sitogasa Sitogasa (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Industrial batik wastewater contains total chromium, a heavy metal that can pollute aquatic environments. This study aims to evaluate the performance of a fixed-bed adsorption reactor in reducing total chromium concentrations in batik wastewater using coconut shell, corn cob, and zeolite adsorbents. The batik wastewater was obtained from Jemursari, Surabaya, with an initial total chromium concentration of 2.349-2.374 mg/L and a pH of 8. The bioadsorbents were prepared through carbonization at 500–600 °C, followed by chemical activation using 3 M H?PO?. The adsorption process was conducted continuously in a 5 L laboratory-scale fixed-bed reactor, with sampling times at 10, 40, 70, and 100 minutes. The results showed that total chromium removal efficiency increased significantly within the first 40 minutes for all adsorbents. The highest removal efficiency was achieved using zeolite at 87.8%, followed by coconut shell at 81.9% and corn cob at 73.1%. The superior performance of zeolite was attributed to its ion-exchange mechanism and physical properties, which are well-suited to continuous-flow systems. Contribution to Sustainable Development Goals (SDGs):SDG 6: Clean Water and SanitationSDG 12: Responsible Consumption and ProductionSDG 11: Sustainable Cities and CommunitiesSDG 14 : Life Below Water